2018
DOI: 10.1186/s13643-018-0707-8
|View full text |Cite
|
Sign up to set email alerts
|

Technology-assisted title and abstract screening for systematic reviews: a retrospective evaluation of the Abstrackr machine learning tool

Abstract: BackgroundMachine learning tools can expedite systematic review (SR) processes by semi-automating citation screening. Abstrackr semi-automates citation screening by predicting relevant records. We evaluated its performance for four screening projects.MethodsWe used a convenience sample of screening projects completed at the Alberta Research Centre for Health Evidence, Edmonton, Canada: three SRs and one descriptive analysis for which we had used SR screening methods. The projects were heterogeneous with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 26 publications
3
102
0
1
Order By: Relevance
“…Specifically, for large reports, potential reductions in screening burden were 4 to 49% (Abstrackr) and 9 to 60% (EPPI-Reviewer). Our findings are consistent with other studies which have found Abstrackr to offer potential gains [7,19,21]. However, to our knowledge, our study is the first to assess EPPI-Reviewer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, for large reports, potential reductions in screening burden were 4 to 49% (Abstrackr) and 9 to 60% (EPPI-Reviewer). Our findings are consistent with other studies which have found Abstrackr to offer potential gains [7,19,21]. However, to our knowledge, our study is the first to assess EPPI-Reviewer.…”
Section: Discussionsupporting
confidence: 92%
“…Both tools are web-based and facilitate citation screening through text-mining tools and machine learning techniques; they employ "active learning," in which ongoing feedback from reviewers is used dynamically to improve predictive accuracy [14,17]. Several studies have incorporated Abstrackr into workflow (e.g., as a second screener) and reported a range of improvements in efficiency [19]. For instance, three studies using Abstrackr for screening citations for new reviews (i.e., not updates) reported significant, but variable workload reductions ranging from 9 to 57% [7,13,17].…”
Section: Tools Of Interest: Abstrackr and Eppi-reviewermentioning
confidence: 99%
“…Automated duplicate checking, and web scraping also led to significant time savings. Despite progress in the use of machine learning to help automate abstract screening [70,71], we concluded this technology is not sufficiently developed to have been applicable without further testing. Innovative methods are much needed, particularly as the size and scope of maps and reviews continue to increase [72,73].…”
Section: Efficiency In the Review Processmentioning
confidence: 99%
“…Because our evaluation was retrospective, we estimated time savings based on a screening rate of two records per minute. Although ambitious, this rate allowed for more conservative estimates of time savings and for comparisons to previous studies that have used the same rate [10,15,16].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previously published studies undertaken at our evidence synthesis centre [10,15,16] have addressed the bene ts (workload and estimated time savings) and risks (omitting relevant studies) of various MLassisted screening approaches in systematic and rapid reviews. We have also explored the usability of some available ML tools [10].…”
Section: Introductionmentioning
confidence: 99%